Therapeutic efficacy of low-dose rituximab for steroid-dependent minimal-change nephrotic syndrome in adults - Li Xiao-wei; Guo Kai-qi; Xu Li; Huang Lan-lan; Li Hui-min (Linchuang shenzangbing zazhi)
Objective To explore the therapeutic efficacy of low-dose rituximab（RTX）for a relapse of steroid-dependent minimal-change nephrotic syndrome（SDMCNS）in adults.Methods From November 2018 to December 2019,8 male SDMCNS patients were retrospectively analyzed.They received low-dose RTX treatment and were followed up for over 18 months.Results The median age was 28.5（18-53）years and the median follow-up period 24.5（18-28）months.And 5 and 3 cases received 2 and 3 intermittent doses of RTX 0.375 g/m2 respectively.None of them had a relapse within 1 year.RTX 0.375 g/m2 was repeated for 4 cases when CD19+ B-cell count dropped to 6.No relapse occurred at the end of follow-up period.A comparison of clinical data at 1 year before and after RTX dosing, hormone dose declined.At the end of follow-up period, the maintenance dose was 7.5（0-20）mg/d.Two discontinued horome and frequency of relapse/hospitalization and incidence of complications decreased markedly.Except for skin rash and pruritus in one case, the remainders had no obvious adverse effects.Conclusion For SDMCNS in adults, using low-dose RTX may be repeated based upon monitoring CD19+ B-cell count.Such a regimen may lower the frequency of relapse and reduce economic expenditures with fewer side effects.